Determinants of Hedge Fund Internal Controls and Fees - Cassar, Gavin; Gerakos, Joseph (The Accounting Review, 2010)
ABSTRACT: We investigate the determinants of hedge fund internal controls and their association with the fees that funds charge investors. Hedge funds are subject to minimal regulation. Hence, hedge fund managers voluntarily implement internal controls, and managers and investors freely contract on fees. We find that internal controls are stronger in funds with higher potential agency costs. Further, internal controls are stronger in funds domiciled in jurisdictions that provide investors with limited legal redress for fraud and financial misstatements. Short selling funds, however, are more likely to protect information about their investment positions by implementing weaker internal controls. With respect to fees, we find that the percentage of positive profits that the manager receives increases in the strength of the fund’s internal controls. Finally, removing the manager from setting and reporting the fund’s official net asset value, along with reputational incentives and monitoring by leverage providers, are all associated with lower likelihoods of future regulatory investigations of fraud and/or financial misstatement.